Rotationally Induced Local Heat Transfer Features in a Two-Pass Cooling Channel: Experimental–Numerical Investigation - David Gutiérrez de Arcos; Christian Waidmann; Rico Poser; Jens von Wolfersdorf; Michael Göhring (International Journal of Turbomachinery, Propulsion and Power)
Turbine blades for modern turbomachinery applications often exhibit complex twisted designs that aim to reduce aerodynamic losses, thereby improving the overall machine performance. This results in intricate internal cooling configurations that change their spanwise orientation with respect to the rotational axis. In the present study, the local heat transfer in a generic two-pass turbine cooling channel is investigated under engine-similar rotating conditions (<semantics>Ro={0<mspace width="0.166667em"></mspace>…<mspace width="0.166667em"></mspace>0.50}</semantics>) through the transient Thermochromic Liquid Crystal (TLC) measurement technique. Three different angles of attack (<semantics>α={−18.5°<mspace width="0.222222em"></mspace>;<mspace width="0.222222em"></mspace>+8°<mspace width="0.222222em"></mspace>;<mspace width="0.222222em"></mspace>+46.5°}</semantics>) are investigated to emulate the heat transfer characteristics in an internal cooling channel of a real turbine blade application at different spanwise positions. A numerical approach based on steady-state Reynolds-averaged Navier–Stokes (RANS) simulations in ANSYS CFX is validated against the experimental method, showing generally good agreement and, thus, qualifying for future heat transfer predictions. Experimental and numerical data clearly demonstrate the substantial impact of the angle of attack on the local heat transfer structure, especially for the radially outward flow of the first passage, owing to the particular Coriolis force direction at each angle of attack. Furthermore, results underscore the strong influence of the rotational speed on the overall heat transfer level, with an enhancement effect for the radially outward flow (first passage) and a reduction effect for the radially inward flow (second passage).